High-thermal-conductivity polyethylene pipe master batch and preparation method thereof

By using a solution-melt method to prepare polyethylene pipes using carbon nanotubes and graphene, a three-dimensional thermally conductive network is formed, which solves the shortcomings of the thermal conductivity and mechanical properties of polyethylene pipes and achieves a synergistic improvement in high thermal conductivity and high toughness.

CN121343264APending Publication Date: 2026-01-16JILIN JIANZHU UNIVERSITY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511629851.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-11-08
Publication Date
2026-01-16

AI Technical Summary

Technical Problem

Polyethylene pipes have poor thermal conductivity, which leads to the slow release of thermal stress and different expansion rates in different parts, which may cause pipe damage. At the same time, the uneven dispersion of inorganic fillers in the polymer matrix leads to the deterioration of mechanical properties.

Method used

High thermal conductivity polyethylene composite masterbatch was prepared by using carbon nanotubes and graphene as thermally conductive fillers via a solution-melt method. The fillers were first ultrasonically dispersed in a solution, and then melt-blended using a twin-screw extruder to form a three-dimensional thermally conductive network. This network was then combined with copolymer elastomers to improve toughness and strength.

Benefits of technology

It achieves a synergistic improvement in high thermal conductivity and good mechanical properties, significantly reduces the thermal permeation threshold, and improves the thermal conductivity and tensile mechanical properties of polyethylene pipes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121343264A_ABST
    Figure CN121343264A_ABST
Patent Text Reader

Abstract

The invention provides a high-thermal-conductivity polyethylene pipe master batch and a preparation method thereof. The master batch comprises polyethylene powder particles, a copolymer elastomer, surface-modified graphene, multi-walled carbon nanotubes and a processing aid. The raw materials are blended in two steps by adopting a solution-melting method, so that the heat-conducting filler is selectively and uniformly dispersed in a polyethylene matrix, and the percolation threshold value is effectively reduced. The two heat-conducting fillers with different shapes are compounded for use, so that a three-dimensional, efficient and stable heat-conducting network can be constructed, and rapid transportation of heat in the three-dimensional direction is realized. The copolymer elastomer is used as a stress concentration point to initiate crazing and a shear band, so that a large amount of impact energy is absorbed, and the effect of toughening polyethylene is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the field of pipe materials, in particular to a master batch special for high-thermal-conductivity polyethylene pipe materials and a preparation method thereof. BACKGROUND

[0002] Polyethylene has excellent chemical stability, chemical corrosion resistance and electrical insulation, and the pipe material made of polyethylene is widely used in the fields of domestic water supply and heating, municipal engineering, agricultural production and construction industry. However, the thermal conductivity of polyethylene is poor, with a thermal conductivity coefficient of only 0.33-0.44 W / (m·K), which cannot meet the performance requirements of heat exchange pipe fittings and limits its application in circulating heat dissipation terminals and ground source heat pump systems. The low thermal conductivity coefficient of polyethylene pipe material will cause the slow release of thermal stress, resulting in different expansion rates at different parts, and the local stress generated may cause the pipe material to be damaged. In order to obtain polyethylene pipe material with high thermal conductivity, a large amount of inorganic thermal conductive filler is generally needed, but the compatibility between the filler and polyethylene is poor, which can easily lead to the deterioration of mechanical properties. Therefore, improving the thermal conductivity coefficient and mechanical properties of polyethylene pipe material has important practical and scientific value for preparing polyethylene heat exchange pipe with excellent comprehensive performance.

[0003] Introducing a filler with high thermal conductivity coefficient into a polyethylene-based composite material is an effective method to improve the heat transfer of the polyethylene-based composite material. Commonly used thermal conductive fillers include carbon fibers, graphite, silicon carbide, boron nitride, graphene and carbon nanotubes, etc. However, in order to obtain excellent thermal conductivity, a certain amount of inorganic filler needs to be added, which leads to the deterioration of the mechanical properties of the composite pipe material. In addition, due to factors such as surface activity, size and aspect ratio of inorganic fillers, the fillers are prone to entanglement, agglomeration and stacking, and it is difficult to disperse uniformly in the polymer matrix, resulting in brittle and easy-to-break pipe material. Therefore, in order to prepare pipe material with high mechanical strength and excellent heat exchange / heat dissipation performance, it is necessary to realize the uniform dispersion of inorganic fillers in the polymer matrix and solve the interaction between the filler / polymer interface.

[0004] CN202310999510 discloses a high-thermal-conductivity composite material and a preparation method. The mixer is used to process expanded graphite and carbon nanotubes together in a polyethylene matrix, which can realize the uniform co-dispersion of the polyethylene matrix and the fillers, and the material can maintain the long-range thermal conduction path established by the graphene and carbon nanotube composite filler in the polyethylene matrix as much as possible, which can significantly improve the thermal conductivity of the composite material.

[0005] CN116410530A discloses a high-thermal-conductivity carbon nanotube composite master batch and a preparation method thereof. After the multi-walled carbon nanotubes are modified by ultrasonic dispersion, the surface hydroxyl groups thereof can react with the compatibilizer, so that the compatibilizer is grafted onto the surface of the multi-walled carbon nanotubes, and effective coating of the multi-walled carbon nanotubes is achieved. The addition of the modified multi-walled carbon nanotubes greatly improves the thermal conductivity of the polyethylene material, so that the special material obtained from the high-thermal-conductivity carbon nanotube composite master batch has good effects in terms of thermal conductivity and impact strength. SUMMARY

[0006] The purpose of the present application is to provide a high-thermal-conductivity polyethylene composite master batch. By adding two kinds of thermal-conductivity fillers, carbon nanotubes and graphene, the thermal conductivity of the floor heating pipe is improved through synergistic effect. The unique isolated network structure formed by the carbon nanotubes and the graphene is most conducive to phonon propagation. Another purpose of the present application is to maintain the high strength and good toughness of the thermal-conductivity composite master batch. By adding a copolymer elastomer, the special material obtained from the composite master batch has good effects in terms of tensile mechanical properties and impact strength.

[0007] The technical solutions adopted by the present application are as follows:

[0008] A high-thermal-conductivity polyethylene pipe master batch comprises the following components: polyethylene powder, copolymer elastomer, graphene filler, multi-walled carbon nanotube filler, surface modifier, and processing aid. The weight fractions of the components in the master batch are as follows:

[0009]

[0010]

[0011] The polyethylene powder has a melt flow rate of 0.50-1.5 g / 10 min and a weight average molecular weight of 5-200,000 at a rated temperature of 190℃ and a rated load of 5 kg.

[0012] The multi-walled carbon nanotubes have a length of 3-12 μm.

[0013] The graphene has a length of 3-15 μm.

[0014] The copolymer elastomer is one of propylene-ethylene copolymer and ethylene-octene copolymer.

[0015] The propylene-ethylene copolymer has a melt flow rate of 9.1 g / 10 min at a rated temperature of 190℃ and a rated load of 2.16 kg.

[0016] The ethylene-octene copolymer has a melt flow rate of 0.5 g / 10 min at a rated temperature of 190℃ and a rated load of 2.16 kg.

[0017] The surface modifier is at least one of 3-aminopropyltriethoxysilane, 3-glycidyl etheroxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-isocyanatepropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, methyltrimethoxysilane, and octyltriethoxysilane.

[0018] The processing aid is at least one of an antioxidant and a lubricant.

[0019] The antioxidant is at least one of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 626.

[0020] The lubricant is at least one of stearic acid, zinc stearate, calcium stearate, polyethylene wax, oxidized polyethylene wax, and polypropylene wax.

[0021] The high thermal conductivity polyethylene pipe masterbatch is prepared by three steps: surface modification of thermally conductive filler, preparation of pre-blended material, and melt blending.

[0022] Step 1: Surface modification of thermally conductive filler

[0023] Graphene and multi-walled carbon nanotubes were mixed at a certain mass ratio and added to a solvent. The mixture was ultrasonically dispersed at 40°C for 2 hours. The flask was then transferred to a magnetic stirrer and stirred at a constant speed for 15 minutes. During stirring, a certain amount of surface modifier was added to the flask to form a uniform conductive filler dispersion liquid. The solvent was one of xylene, toluene, or an N-methylpyrrolidone / xylene mixture.

[0024] Step 2: Preparation of pre-blended materials

[0025] A certain mass of polyethylene granules was added to a conductive filler dispersion liquid, and the mixture was continuously stirred at a stirring speed of 800–1500 rpm. The temperature was heated to 100–130°C, refluxed, and condensed. Stirring continued for at least 1 hour until the polyethylene was completely dissolved and the solution became homogeneous and translucent. The blended solution was cast onto a glass plate and allowed to stand at room temperature and atmospheric pressure for 12 hours. The pre-cured sample was then transferred to a vacuum oven and vacuum dried at 50–60°C for 48 hours to obtain the polyethylene-based composite material.

[0026] Step 3: Melt blending

[0027] Polyethylene-based composite material, copolymer elastomer, and processing aids are mixed uniformly to obtain a mixture. The mixture is then fed into a twin-screw extruder for extrusion granulation to obtain the high thermal conductivity polyethylene composite material masterbatch. The processing temperature of the twin-screw extruder barrel is 170-200℃, with zone one at 170-180℃, zone two at 175-185℃, zone three at 180-190℃, zone four at 190-200℃, and zone five at 170-180℃.

[0028] Beneficial effects of the present invention

[0029] (1) Graphene is a two-dimensional sheet structure with extremely high in-plane thermal conductivity (up to 3000-5000 W / mK). However, in composite materials, graphene sheets tend to stack randomly, and heat can only be conducted within the plane of the sheets. When heat is transferred from one sheet to another, it encounters huge interfacial thermal resistance. There are strong van der Waals forces between graphene sheets, which easily cause them to re-aggregate. This not only reduces the effective filling amount but also increases the interfacial thermal resistance, hindering heat transfer. Carbon nanotubes are one-dimensional tubular structures with excellent axial thermal conductivity (up to 3000-3500 W / mK). However, in composite materials, carbon nanotubes are in "point contact," with a very small contact area. This results in extremely high interfacial thermal resistance when heat is transferred from one carbon nanotube to another, easily forming a thermal bottleneck. Carbon nanotubes also tend to entangle and clump together, making it difficult to disperse uniformly in the polymer matrix to form an effective thermally conductive network. When carbon nanotubes and graphene are used together, they can compensate for each other's shortcomings and jointly construct a three-dimensional, efficient, and stable heat-conducting network. Carbon nanotubes act like tiny bridges, weaving between graphene sheets. They connect graphene sheets that were originally separated by the polymer matrix and could only make face-to-face contact. Heat is rapidly conducted within the graphene plane, and upon reaching the junction with the carbon nanotubes, it can be efficiently conducted to another graphene sheet or a more distant area of ​​the heat-conducting network via this "shortcut." This greatly overcomes the problem of high interfacial thermal resistance between graphene sheets, enabling rapid three-dimensional heat transport.

[0030] (2) High thermal conductivity polyethylene composite masterbatch was prepared using a solution-melt method. Graphene and carbon nanotubes have high surface energy and are prone to re-agglomeration in molten polyethylene. The solution method utilizes the "de-agglomeration" effect of the solvent and the ultrasonic dispersion capability to fully disperse the filler at the molecular level in the polyethylene solution. After the solvent is removed, the polymer molecular chains adsorb and wrap around the surface of the dispersed nanofiller, forming a "pre-isolated" structure. For carbon nanotubes and graphene, their excellent performance is closely related to their intact structure and high aspect ratio. The solution-melt method first achieves dispersion through gentle ultrasonication of the solution, avoiding the structural damage to the filler that may be caused by the extremely strong shear force required by the direct melting method, thus better preserving the inherent properties of the filler. In the solution stage, the polyethylene molecular chains and the filler have more contact time and opportunities, and can achieve better interfacial bonding through interactions such as van der Waals forces and π-π stacking. This good interface is beneficial for stress transfer and reducing phonon scattering. Since the conductive filler is already sufficiently dispersed and "fixed" within the polyethylene chains in the first step, the main task in the second step of melt blending is further homogenization, rather than forced deagglomeration. This makes it easier for the filler to contact each other in the matrix, thus forming a continuous three-dimensional thermally conductive network with a lower filler content, significantly reducing the percolation threshold. The solution-melt method moves the energy-intensive solution dispersion step forward, and the subsequent melt blending step utilizes existing mature and efficient twin-screw extruders for continuous, large-scale production, balancing effectiveness and efficiency.

[0031] (3) In the "sea-island" structure blend of polyethylene and copolymer elastomer, due to the different interfacial energies between the two components and the filler, the conductive filler will be selectively distributed in one phase or at the interface between the two phases. The conductive filler is mixed with polyethylene in the first step of the solution-melt blending process, so that it is selectively dispersed in the continuous polyethylene phase, which can significantly reduce the thermal conductivity percolation threshold and achieve a higher thermal conductivity with less filler. This avoids the increase in material cost, processing difficulties, and deterioration of mechanical properties caused by excessive filler. The elastomer, as a stress concentration point, induces crazes and shear bands, absorbs a large amount of impact energy, and plays a role in toughening polyethylene. The filler network selectively dispersed in the polyethylene phase can play a role similar to a "skeleton", restricting the movement of polymer chains, thereby improving the modulus and strength of the composite material. In this system, the elastomer is responsible for toughening, and the selectively dispersed filler is responsible for thermal conductivity. The two perform their respective functions and achieve the synergistic unity of the seemingly contradictory goals of "high thermal conductivity" and "high toughness". Attached Figure Description

[0032] Figure 1 The thermal conductivity diagrams are for Comparative Examples 2-3 and Examples 1-4. Detailed Implementation

[0033] The present invention will now be described in detail with reference to specific embodiments, but these embodiments are not to be construed as limiting the scope of protection of the present invention in any sense.

[0034] Example 1

[0035] A high thermal conductivity polyethylene pipe masterbatch is prepared from the following raw materials in parts by weight:

[0036]

[0037] In this embodiment, the copolymer elastomer is a propylene-ethylene copolymer; the antioxidant in this embodiment is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant in this embodiment is a mixture of zinc stearate and polyethylene wax in a mass ratio of 1:1.

[0038] Step 1: Surface modification of thermally conductive filler

[0039] Graphene and multi-walled carbon nanotubes were mixed at a certain mass ratio and added to a solvent. The mixture was ultrasonically dispersed at 40°C for 2 hours. The flask was then transferred to a magnetic stirrer and stirred at a constant speed for 15 minutes. During stirring, a certain amount of surface modifier was added to the flask to form a uniform conductive filler dispersion liquid. In this embodiment, the surface modifier was KH-550 (aminosilane), and the solvent was an N-methylpyrrolidone / xylene mixed solvent.

[0040] Step 2: Preparation of pre-blended materials

[0041] A certain mass of polyethylene granules was added to a conductive filler dispersion liquid, and the mixture was continuously stirred at a stirring speed of 1000 rpm. The mixture was heated to 100℃, refluxed, and condensed, and stirred for at least 1 hour until the polyethylene was completely dissolved and the solution became homogeneous and translucent. The blended solution was cast onto a glass plate and allowed to stand at room temperature and atmospheric pressure for 12 hours. The pre-cured sample was then transferred to a vacuum oven and vacuum dried at 50℃ for 48 hours to obtain the polyethylene-based composite material.

[0042] Step 3: Melt blending

[0043] Polyethylene-based composite material, copolymer elastomer, antioxidant and lubricant are mixed evenly to obtain a mixture; the mixture is added to a twin-screw extruder, and the temperature of zone one is set to 170℃, zone two to 175℃, zone three to 180℃, zone four to 190℃, and zone five to 180℃, and extruded and granulated to obtain the high thermal conductivity polyethylene composite material masterbatch.

[0044] Example 2

[0045] A high thermal conductivity polyethylene pipe masterbatch is prepared from the following raw materials in parts by weight:

[0046]

[0047]

[0048] In this embodiment, the copolymer elastomer is a propylene-ethylene copolymer; the antioxidant in this embodiment is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant in this embodiment is a mixture of zinc stearate and polyethylene wax in a mass ratio of 1:1.

[0049] Step 1: Surface modification of thermally conductive filler

[0050] Graphene and multi-walled carbon nanotubes were mixed at a certain mass ratio and added to a solvent. The mixture was ultrasonically dispersed at 40°C for 2 hours. The flask was then transferred to a magnetic stirrer and stirred at a constant speed for 15 minutes. During stirring, a certain amount of surface modifier was added to the flask to form a uniform conductive filler dispersion liquid. In this embodiment, the surface modifier was KH-550 (aminosilane), and the solvent was an N-methylpyrrolidone / xylene mixed solvent.

[0051] Step 2: Preparation of pre-blended materials

[0052] A certain mass of polyethylene granules was added to a conductive filler dispersion liquid, and the mixture was continuously stirred at a stirring speed of 1000 rpm. The mixture was heated to 100℃, refluxed, and condensed, and stirred for at least 1 hour until the polyethylene was completely dissolved and the solution became homogeneous and translucent. The blended solution was cast onto a glass plate and allowed to stand at room temperature and atmospheric pressure for 12 hours. The pre-cured sample was then transferred to a vacuum oven and vacuum dried at 50℃ for 48 hours to obtain the polyethylene-based composite material.

[0053] Step 3: Melt blending

[0054] Polyethylene-based composite material, copolymer elastomer, antioxidant and lubricant are mixed evenly to obtain a mixture; the mixture is added to a twin-screw extruder, and the temperature of zone one is set to 170℃, zone two to 175℃, zone three to 180℃, zone four to 190℃, and zone five to 180℃, and extruded and granulated to obtain the high thermal conductivity polyethylene composite material masterbatch.

[0055] Example 3

[0056] A high thermal conductivity polyethylene pipe masterbatch is prepared from the following raw materials in parts by weight:

[0057]

[0058] In this embodiment, the copolymer elastomer is a propylene-ethylene copolymer; the antioxidant in this embodiment is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant in this embodiment is a mixture of zinc stearate and polyethylene wax in a mass ratio of 1:1.

[0059] Step 1: Surface modification of thermally conductive filler

[0060] Graphene and multi-walled carbon nanotubes were mixed at a certain mass ratio and added to a solvent. The mixture was ultrasonically dispersed at 40°C for 2 hours. The flask was then transferred to a magnetic stirrer and stirred at a constant speed for 15 minutes. During stirring, a certain amount of surface modifier was added to the flask to form a uniform conductive filler dispersion liquid. In this embodiment, the surface modifier was KH-550 (aminosilane), and the solvent was an N-methylpyrrolidone / xylene mixed solvent.

[0061] Step 2: Preparation of pre-blended materials

[0062] A certain mass of polyethylene granules was added to a conductive filler dispersion liquid, and the mixture was continuously stirred at a stirring speed of 1000 rpm. The mixture was heated to 100℃, refluxed, and condensed, and stirred for at least 1 hour until the polyethylene was completely dissolved and the solution became homogeneous and translucent. The blended solution was cast onto a glass plate and allowed to stand at room temperature and atmospheric pressure for 12 hours. The pre-cured sample was then transferred to a vacuum oven and vacuum dried at 50℃ for 48 hours to obtain the polyethylene-based composite material.

[0063] Step 3: Melt blending

[0064] Polyethylene-based composite material, copolymer elastomer, antioxidant and lubricant are mixed evenly to obtain a mixture; the mixture is added to a twin-screw extruder, and the temperature of zone one is set to 170℃, zone two to 175℃, zone three to 180℃, zone four to 190℃, and zone five to 180℃, and extruded and granulated to obtain the high thermal conductivity polyethylene composite material masterbatch.

[0065] Example 4

[0066] A high thermal conductivity polyethylene pipe masterbatch is prepared from the following raw materials in parts by weight:

[0067]

[0068] In this embodiment, the copolymer elastomer is a propylene-ethylene copolymer; the antioxidant in this embodiment is a mixture of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1; the lubricant in this embodiment is a mixture of zinc stearate and polyethylene wax in a mass ratio of 1:1.

[0069] Step 1: Surface modification of thermally conductive filler

[0070] Graphene and multi-walled carbon nanotubes were mixed at a certain mass ratio and added to a solvent. The mixture was ultrasonically dispersed at 40°C for 2 hours. The flask was then transferred to a magnetic stirrer and stirred at a constant speed for 15 minutes. During stirring, a certain amount of surface modifier was added to the flask to form a uniform conductive filler dispersion liquid. In this embodiment, the surface modifier was KH-550 (aminosilane), and the solvent was an N-methylpyrrolidone / xylene mixed solvent.

[0071] Step 2: Preparation of pre-blended materials

[0072] A certain mass of polyethylene granules was added to a conductive filler dispersion liquid, and the mixture was continuously stirred at a stirring speed of 1000 rpm. The mixture was heated to 100℃, refluxed, and condensed, and stirred for at least 1 hour until the polyethylene was completely dissolved and the solution became homogeneous and translucent. The blended solution was cast onto a glass plate and allowed to stand at room temperature and atmospheric pressure for 12 hours. The pre-cured sample was then transferred to a vacuum oven and vacuum dried at 50℃ for 48 hours to obtain the polyethylene-based composite material.

[0073] Step 3: Melt blending

[0074] Polyethylene-based composite material, copolymer elastomer, antioxidant and lubricant are mixed evenly to obtain a mixture; the mixture is added to a twin-screw extruder, and the temperature of zone one is set to 170℃, zone two to 175℃, zone three to 180℃, zone four to 190℃, and zone five to 180℃, and extruded and granulated to obtain the high thermal conductivity polyethylene composite material masterbatch.

[0075] Comparative Example 1

[0076] A polyethylene pipe masterbatch, with the same raw material addition amounts as in Example 1, except that after surface modification of the thermally conductive filler in step 2, it was not pre-blended but directly dried. It was then mixed with polyethylene granules, copolymer elastomer, antioxidant, and lubricant, extruded in an extruder, and samples were prepared and tested.

[0077] Comparative Example 2

[0078] A polyethylene pipe masterbatch is prepared using the same raw materials and dosage as in Example 1, except that no copolymer elastomer is added.

[0079] Comparative Example 3

[0080] A polyethylene pipe masterbatch is prepared using the same raw materials and dosage as in Example 1, except that graphene is not added.

[0081] Comparative Example 4

[0082] A polyethylene pipe masterbatch is prepared using the same raw materials and dosage as in Example 1, except that carbon nanotubes are not added.

[0083] Performance testing:

[0084] The masterbatches obtained in Examples 1, 2, 3, and 4 and Comparative Examples 1, 2, 3, and 4 were tested for the following performance indicators:

[0085] 1. Tensile mechanical properties: The yield stress of the examples and comparative examples was tested according to GB / T 1040.1 standard.

[0086] 2. Impact strength: The impact strength of the notched cantilever beams in the examples and comparative examples was tested according to GB / T 1843-2008 standard.

[0087] 3. Thermal conductivity: The masterbatch was prepared into 100cm×100cm×10mm samples, and the thermal conductivity of the examples and comparative examples was tested according to GB / T 3399-1982 standard.

[0088] The test results are shown in Table 1.

[0089]

[0090] As shown in Table 1, the yield strength, impact strength, and thermal conductivity of Example 1 are all greater than those of Comparative Example 1. The examples used a solution-melt method to prepare high thermal conductivity polyethylene composite masterbatch, with thermally conductive fillers selectively and uniformly dispersed in the polyethylene matrix phase. The resulting masterbatch exhibits better mechanical and thermal conductivity properties. The impact strength and thermal conductivity of Example 1 are higher than those of Comparative Example 2 because the elastomer significantly improves the toughness of the masterbatch. Furthermore, the selective dispersion of the thermally conductive filler in the polyethylene matrix significantly reduces the thermal percolation threshold, resulting in better thermal conductivity for the same content of thermally conductive filler. The thermal conductivity and yield strength of Examples 3 and 4 are significantly higher than those of Comparative Examples 3 and 4 because when carbon nanotubes and graphene are used in combination, they can compensate for each other's deficiencies and jointly construct a three-dimensional, efficient, and stable thermally conductive network. The above descriptions are merely preferred embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Those skilled in the art can make various corresponding modifications according to the present invention, but these corresponding modifications should all fall within the scope of protection of the present invention.

Claims

1. A high thermal conductive polyethylene pipe masterbatch, characterized by The masterbatch comprises polyethylene powder, copolymer elastomer, graphene filler, multi-walled carbon nanotube filler, surface modifier, processing aid.

2. The high thermal conductive polyethylene pipe masterbatch according to claim 1, characterized in that The preparation method comprises three steps of surface modification of the heat-conducting filler, preparation of a pre-blend, and melt blending, and specifically as follows. Step one, surface modification of the heat-conducting filler, mix graphene and multi-walled carbon nanotube at a certain mass ratio, add to a solvent, ultrasonic dispersion at 40℃ for 2h, move the flask to a magnetic stirrer, uniform stirring for 15min, add a certain amount of surface modifier to the flask during stirring, form a uniform conductive filler dispersion liquid, the solvent is one of dimethylbenzene, toluene, N-methylpyrrolidone / dimethylbenzene mixed solvent; Step two, preparation of a pre-blend, add a certain mass of polyethylene pellets to the conductive filler dispersion liquid, continue stirring, stirring rate 800-1500rpm, heating temperature 100-130℃, reflux condensation, stir for more than 1h until the polyethylene is completely dissolved, the solution becomes uniform and translucent, pour the blended solution onto a glass plate, then stand at room temperature under normal pressure for 12h, then transfer the preliminarily solidified sample to a vacuum oven, vacuum drying at a temperature range of 50-60℃ for 48h to obtain a polyethylene-based composite material; Step three, melt blending, mix the polyethylene-based composite material, copolymer elastomer and processing aid uniformly to obtain a mixture; add the mixture to a double-screw extruder, extrude and granulate to obtain a high-heat-conducting polyethylene pipe masterbatch; the processing temperature of the double-screw extruder barrel is 170-200℃, wherein the temperature of the first zone is 170-180℃, the temperature of the second zone is 175-185℃, the temperature of the third zone is 180-190℃, the temperature of the fourth zone is 190-200℃, and the temperature of the fifth zone is 170-180℃.

3. The high thermal conductive polyethylene pipe masterbatch according to claim 1, characterized in that, The weight parts of each component in the masterbatch are as follows: polyethylene powder 100 parts, copolymer elastomer 10-30 parts, graphene 1-5 parts, multi-walled carbon nanotube 1-5 parts, surface modifier 1-3 parts, and processing aid 1-3 parts.

4. The high thermal conductive polyethylene pipe masterbatch according to claim 1, wherein, The copolymer elastomer is one of propylene-ethylene copolymer and ethylene-octene copolymer.

5. The high thermal conductive polyethylene pipe masterbatch as claimed in claim 1, wherein, The surface modifier is at least one of 3-aminopropyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, 3-aminopropyltrimethoxysilane, 3-isocyanatopropyltriethoxysilane, vinyltrimethoxysilane, vinyltriethoxysilane, methyltrimethoxysilane, and octyltriethoxysilane.

6. The high thermal conductive polyethylene pipe masterbatch according to claim 1, wherein, The processing aid is at least one of an antioxidant and a lubricant.

7. The antioxidant according to claim 6 is one or several of antioxidant 1010, antioxidant 168, antioxidant 1076, and antioxidant 626.

8. The lubricant according to claim 6 is one or several of stearic acid, zinc stearate, calcium stearate, polyethylene wax, oxidized polyethylene wax, and polypropylene wax.

Citation Information

Patent Citations

  • High-thermal-conductivity composite material, preparation method and high-efficiency radiating tube prepared from high-thermal-conductivity composite material

    CN117050408A